The Influence of Education, Mother’s Attitude and Cadres’ Service on Utilization of Posyandu in South Tapanuli, North Sumatera - Wilda Zulihartika Nasution; Destanul Aulia; Zulhaida Lubis (BIRCU, 2020)
Posyandu as a means of monitoring the growth of toddlers in order to detect problems with growth disorders. Child considering conducted at Posyandu is an effort by the community to monitor the growth of toddler so that community participation is needed. Sayur Matinggi Health Center has an under-targeted program of Posyandu service coverage for toddlers where the percentage of community participation only reaches 53% while the national target coverage is 80%. The type of research used with analytical survey with an sequential explanatory approach. The sample in this study is determine by taking the entire population to be subject of research, as many as 96 toddler’s mothers. This research was conducted at Sayur Matinggi community health centre from Januari to November 2018. The results of the multiple logistic regression test analyses showed that the caders’ service was the dominant factor influencing the utilization of posyandu Sayur Matinggi community health center. The researcher’s suggestion in this research is posyandu cadres should be more active in developing appropriate and interesting activities so that mothers become more active in implementing posyandu and health for their toddlers.